Pelatihan Pembuatan Bunga dari Kawat Bulu sebagai Upaya Peningkatan Kualitas SDM dalam Pembelajaran Seni di Sekolah Dasar - Helda Susianti; Dora Palupi; Yus Dwi Yanti; Mahmudin Mahmudin; Muhamad Galy Njoman Ari Pribowo; Better Swengky; Amanda Saputri (Yayasan Darussalam Bengkulu, 2026)
Arts and crafts learning in elementary schools (ES) is often considered less interesting due to the minimal use of interactive learning media, resulting in low student interest and understanding. This community service program aims to improve the quality of arts learning and student skills through training in making flowers from wire feathers as a creative and applicable medium. The method used is a participatory approach through socialization, demonstrations, direct practice, and mentoring for teachers. This activity was carried out from November - December 2025. The results of the activity showed an increase in student creativity, skills, and interest in learning. In addition, this provided innovation in developing interesting and contextual learning media. This activity also instilled the value of sustainability by utilizing simple, environmentally friendly materials. Overall, this community service had a positive impact in creating more interactive, enjoyable, and meaningful arts learning for students elementary schools (ES).